INNOVATIONS IN CONTROL COMPLIANCE WITH THE LABOR LEGISLATION - Калюга, Александр; Калюга, Евгения (SWorldJournal, 2022)
The need to amend the current Code of Labor Laws (adopted in 1971) is due to political and economic factors. The prepared draft of the Labor Code provides for five main innovations: all labor relations must be based on a contract; the employer has the ri